Effect of micronutrient status on natural killer cell immune function in healthy free-living subjects aged >/=90 y - Ravaglia, G; Forti, P; Maioli, F; Bastagli, L; Facchini, A; Mariani, E; Savarino, L; Sassi, S; Cucinotta, D; Lenaz, G (The American journal of clinical nutrition, 2000)
Natural killer (NK) cells play a role in natural immunity against tumor and infected cells. Advanced aging is associated with functional impairment of NK cells and increased susceptibility to nutritional deficiencies. Our objective was to test whether micronutrient status affects NK cell activity in an older population. The relations between NK cell variables (percentage of leukocytes and cytotoxicity) and blood concentrations of selected micronutrients were studied in 62 healthy, free-living northern Italian subjects (25 men, 37 women) aged 90-106 y. Anthropometric measurements were also made. All subjects were well nourished according to age-specific anthropometric norms but many of them had micronutrient deficiencies. The prevalence of micronutrient deficiency was highest for selenium (in approximately 50% of both sexes), zinc (in 52% of men and 41% of women), and vitamin B-6 (in 40% of men and 59% of women), followed by vitamin A (in 16% of men and 27% of women) and vitamin E, vitamin B-12, and folate (each in <10% of both sexes). Ubiquinone-10 status was inadequate in 40% of women and 24% of men (P = 0.02). The percentage of NK cells was associated with serum zinc (men: r = 0.573, P = 0. 007; women: r = 0.373, P = 0.031) and selenium (women: r = 0.409, P = 0.018) concentrations. In women only, NK cell cytotoxicity at different effector-target cell ratios was positively associated with plasma vitamin E and ubiquinone-10 concentrations (P < 0.05). No significant associations with NK cell variables were found for the other measured nutrients. The results of this study strengthen the hypothesis that individual micronutrients may affect the number and function of NK cells in old age. The study also confirms the high prevalence of micronutrient deficiencies in healthy and apparently well-nourished persons aged >/=90 y.